Gear Video 3: Worm Gears - Tomasi, Christopher (McGraw-Hill's AccessEngineering., 2011)
This video illustrates the thread forms found on the worm and how they mesh with the worm gear, as shown in Figures 8.3.16 and 8.3.17. It discusses the advantages and disadvantages of using a worm, as well as worm gear applications.